Analisis Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja di Rumah Sakit Pekanbaru - Purnawati Rahayu, Endang; Harnani, Yessi; Makomulamin, Makomulamin (Jurnal Kesehatan Komunitas, 2025)
The Occupational Health and Safety Management System (OSHMS) of the hospital ensures that medical personnel, non-medical personnel, patients, and visitors are in a safe and comfortable environment. Activities carried out at Pekanbaru Hospital have the potential for hazards. The purpose of this study was to analyze the implementation of OSHMS in hospitals in Pekanbaru City. This research method employed a qualitative approach, utilizing a case study research design with a content analysis component. The informants in this study consisted of 8 people, including the main informant (a doctor, nurse, or midwife) and supporting informants (the chairman and members of the Hospital K3 committee, the Head of Administration, the Head of Service and Nursing, and the Head of Medical and Non-Medical Support). The data analysis techniques employed were data reduction, data presentation, coding categories, and conclusions. The results of the study are hospital policies regarding OHS, with the formation of a hospital OHS committee, which the hospital director has approved, and OHS planning has been carried out with hazard identification. The hospital had made efforts to control hazards. OHS implementation was carried out by Permenkes No. 66 of 2016, which concerns the implementation of OHS in hospitals. Monitoring and evaluation of performance had also been carried out in the hospital through an internal audit of the hospital's OSHMS. To improve the implementation of OHS.